Peningkatan Wawasan Masyarakat Medan Johor Tentang Promosi Jabatan, Rekan Kerja, dan Kepuasan Kerja Pegawai - Juniarti Juniarti; Nasution, Sarifa Ulfa (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of this community service is to increase the understanding of the Medan Johor community about job promotion, coworkers, and employee job satisfaction. The specific target in this community service is that the people of Medan Johor sub-district know what promotions are, coworkers, and employee job satisfaction. The materials presented in this community service are: what is job promotion, coworkers, and employee job satisfaction. Which in relation will affect the improvement of employee work in Medan Johor sub-district so that the community gets solutions to job promotions, coworkers, and employee job satisfaction. From this community service, the results show that the community of Medan Johor sub-district has known and understood the importance of insight into job promotions, coworkers, and employee job satisfaction so as to improve work performance.